EVALUASI POSISI MAKSILA DAN MANDIBULA SECARA SEFALOMETRIK SETELAH PERAWATAN ORTODONTI CEKAT BERDASARKAN ANALISIS STEINER DAN McNAMARA (LAPORAN PENELITIAN) - D. S. Hartono; H. S. Anggani; M. Karmiati (Faculty of Dentistry, Universitas Indonesia, 2015)
The purpose of this study was to evaluate the changes of maxillary and mandibular sagital position relative to cranial base. The subject of this research was patient with bimaxillary protrusion having orthodontic treatment and four first premolars extraction. The maxillary and mandibular position changes were measured by angular and linear parameters. Angular parameter as described by Steiner's analysis were SNA and SNB angles. Linear parameter as described by McNamara's analysis were point A and Pogonion relative to nasion perpendicular. The results of both groups was compared statistically and differences quantified using paired t-test. There was no significant changes in position of maxillar relative to cranial base. On the other hand, significant changes were found in position of mandibula relative to cranial base.